Characterization of uranium bearing material using X-ray fluorescence and direct gamma-rays measurement techniques - Mujaini M.; Chankow N.; Yusoff M.Z.; Hamid N.A. (American Institute of Physics Inc., 2023)
Uranium ore can be easily detected due to various gamma-ray energies emitted from uranium daughters particularly from 238U daughters such as 214Bi, 214Pb and 226Ra. After uranium is extracted from uranium ore, only low energy gamma-rays emitted from 235U may be detected if the detector is placed in close contact to the specimen. In this research, identification and characterization of uranium bearing materials is experimentally investigated using direct measurement of gamma-rays from 235U in combination with the X-ray fluorescence (XRF) technique. Measurement of gamma-rays can be conducted by using high purity germanium (HPGe) detector or cadmium telluride (CdTe) detector while a 57Coradioisotope-excited XRF spectrometer using CdTe detector is used for elemental analysis. The proposed technique was tested with various uranium bearing specimens containing natural, depleted and enriched uranium in both metallic and powder forms. 2016 AIP Publishing LLC.